Centro y áreas laterales: formación del celtibérico sobre el fondo del celta peninsular hispano (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
After reviewing the different archaeological and linguistic theories accounting for the Hispanic Celticity, Hispania´s Celtic is explained as an old stage of the  Celtic branch, from which Celtiberian developed on the Peninsula as a central linguistic area (with more than a dozen innovatory isoglosses), while remnants of the pre-Celtiberian phase,  pre- served in the periphery (cf. Bartoli´s norma delle aree laterali), are still to be found in part of the Hispano-Celtic corpus. Celtiberian as the lan- guage of the central area may be distinguished from the marginal territories by approximately twenty isoglosses. In this context, a  number of  new etymological approaches is offered.